1981
DOI: 10.1007/bf01477288
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis imperfecta: Biochemical and clinical evaluation of 13 cases

Abstract: Skin fibroblasts were cultured from 13 patients with Osteogenesis imperfecta and collagen biosynthesis was investigated in vitro. In those patients characterised by only mild manifestations of the disease, the ratio of collagen types I and III was disturbed. By contrast, fibroblasts obtained from patients with Osteogenesis imperfecta of a more severe type synthesised collagen types I/III in a normal ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This article must therefore be hereby marked "advertisement" in accordance with 18 U. S. C. §1734 solely to indicate this fact. tains a decreased ratio of type I to type III collagen (7) and that dermal fibroblasts from affected patients produce a decreased ratio oftype I to type III collagen in culture (5). Analysis ofskin and cell culture medium of01 and control cells confirmed these results and, in addition, demonstrated that the production of total collagenous protein by the OI cells was decreased to about halfof the control levels (Table 2).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…This article must therefore be hereby marked "advertisement" in accordance with 18 U. S. C. §1734 solely to indicate this fact. tains a decreased ratio of type I to type III collagen (7) and that dermal fibroblasts from affected patients produce a decreased ratio oftype I to type III collagen in culture (5). Analysis ofskin and cell culture medium of01 and control cells confirmed these results and, in addition, demonstrated that the production of total collagenous protein by the OI cells was decreased to about halfof the control levels (Table 2).…”
mentioning
confidence: 84%
“…Cultures were matched for passage (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) Other Procedures. Collagenase digestions were performed with purified bacterial collagenase (Advance Biofactures, Lynnbrook, NY) by using standard methods (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with 01, mainly defects of type I collagen have been identified. Thus, reduced synthesis of type I, leading to a relative increase of type III collagen has been reported [57][58][59] and the collagen chains have been found to be over-hydroxylated [60][61][62], which was accompanied by an increased content of glucosyl and galactosyl residues. In addition, some patients were characterized by a high degradation of collagen and by the formation of IXI (I) trimers lacking the 1X2(I) chain [63].…”
Section: Diseases Involving the Extracellular Matrixmentioning
confidence: 99%
“…An increased type Ill/type I collagen ratio has been described in patients with mild, severe and lethal OI by several authors [64][65][66][67], One of these cell lines, derived from a patient with a mild type of OI, also failed to synthesize the a2-chain of type I collagen in a previous re port [68], The same defect, namely the ab sence of the a2-chain in type I collagen, has since then been described in another cell line derived from a patient with moderate OI [69]. Increased hyaluronic acid synthesis by skin fibroblasts derived from patients with OI has also been reported [70].…”
Section: Osteogenesis Imperfectamentioning
confidence: 99%